EXPRESSION OF MOTION EQUATIONS FROM VECTOR FORM TO SPHERICAL COORDINATES - MASIBAYI, ANDREW; CYPRIAN, O. S.; OKELO, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
Navier-Stokes equations are the equations of conservation of linear momentum. In this paper we express this type of equation from vector form to spherical co-ordinates. We refer to some equations in this paper from our first paper for the readability of this second paper.